Edukasi Pentingnya Asi Eksklusif Pada 1000 Hari Pertama Kehidupan Anak - Intan Sari; Ana Sapitri; Maria Septiana (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2022)
From an early age children's growth and development requires attention to get a great opportunity so that the growth and development process can take place properly. Parents need to get knowledge about the golden age period and what needs to be prepared in dealing with this period, so that in order to reduce child morbidity and mortality, the United Nations Children's Fund (UNICEF) and the World Health Organization (WHO) strongly recommend that children should only be given water. Mother's milk (ASI) for at least six months. Solid food should be given after the child is 6 months old, and breastfeeding is continued until the child is two years old. The purpose of this activity is to educate parents, especially mothers, to give exclusive breastfeeding to their children, especially in the work area of the Sukajadi Public Health Center, Prabumulih City. . The method used in this activity is lectures, discussions and training on breastfeeding activities correctly, this community service activity was carried out at the Sukajadi Health Center, Prabumulih City from November 01st-06th , 2021, it went smoothly and got a good response and enthusiastic community. Each participant is given a message about the importance of exclusive breastfeeding.